2015
DOI: 10.1155/2015/549013
|View full text |Cite|
|
Sign up to set email alerts
|

Late Onset Traumatic Diaphragmatic Herniation Leading to Intestinal Obstruction and Pancreatitis: Two Separate Cases

Abstract: Although diaphragmatic injuries caused by blunt or penetrating trauma are rare entities, they are the most commonly misdiagnosed injuries in trauma patients and occur in approximately 3–7% of all abdominal or thoracic traumas. Acute pancreatitis secondary to late presenting diaphragmatic hernia is very rare. Here we present two separate cases: one with acute bowel obstruction and the other with acute pancreatitis secondary to late onset traumatic diaphragmatic hernia (three and twenty-eight years after chest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…One reported a man with a right-sided traumatic diaphragmatic hernia 28 years ago presented AP. [ 9 ] The other reported a 68-year-old man presented AP with a history of hiatal hernia. [ 10 ] They all had recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…One reported a man with a right-sided traumatic diaphragmatic hernia 28 years ago presented AP. [ 9 ] The other reported a 68-year-old man presented AP with a history of hiatal hernia. [ 10 ] They all had recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of diaphragmatic hernia is accomplished by laparotomy. 10 F I G U R E 1 Spiral CT scan of abdomen and pelvic with contrast before and after operation Dinc, et al 11 presented two cases of late onset of diaphragmatic herniation 3 and 28 years following chest trauma, respectively. The hernia was complicated by bowel obstruction and acute pancreatitis and was successfully managed surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Dinc, et al 11 presented two cases of late onset of diaphragmatic herniation 3 and 28 years following chest trauma, respectively. The hernia was complicated by bowel obstruction and acute pancreatitis and was successfully managed surgically.…”
Section: Discussionmentioning
confidence: 99%
“…The Case study of this woork is very rare; only 9 similar cases were reported in the literature [ 3 ]; and is charachterized by an atypical chest presentation of acute pancreatitis and an unusual etiology consisting of a post-traumatic diaphragmatic hernia.…”
Section: Introductionmentioning
confidence: 99%